Analisis Dampak Depresiasi Rupiah Terhadap Profitabilitas Perusahaan Publik: Peran Transformasi Digital Pada Emiten Bursa Efek Indonesia - Nur Hidayah; Ratih Dewi Titisari Haryana (MAPAN: Jurnal Manajemen Akuntansi Palapa Nusantara, 2026)
This study aims to analyze the impact of rupiah depreciation on public company profitability and examine the role of digital transformation as an adaptive mechanism in responding to external economic pressures. Exchange rate volatility is one of the macroeconomic factors affecting corporate cost structures, particularly firms dependent on imported raw materials, foreign currency debt, and international trade activities. On the other hand, digital transformation enables firms to improve operational efficiency through business process automation, digital accounting systems, enterprise resource planning (ERP), and supply chain optimization. This study applies a quantitative approach using panel data of non-financial companies listed on the Indonesia Stock Exchange during 2020–2025. Profitability is measured using Return on Assets (ROA), rupiah depreciation is measured based on Bank Indonesia exchange rates, while digital transformation is measured using digital disclosure index from annual reports. The analysis method employs Moderated Regression Analysis (MRA). The study contributes theoretically to accounting literature by integrating macroeconomic factors and corporate digitalization in explaining financial performance.